Water Flow Behavior and Storage Potential of the Semi-Arid Ephemeral River System in the Mara Basin of Kenya - Wekesa, Sospeter Simiyu; Stigter, Tibor Yvan; Olang, Luke O.; Oloo, Francis; Fouchy, Kelly; McClain, Michael E. (Frontiers in Environmental Science, 2020)
Alluvial corridors of ephemeral river systems provide viable opportunities for natural water storage in dry lands. Whilst alluvial corridors are widely recognized as water buffers, particularly for areas experiencing constant water scarcity, little research has been undertaken in Sub-Saharan Africa to explore their hydrological variability and water resource potential as alternative water sources for nearby communities. This study investigated the water flow behavior and storage potential of an ephemeral river system in the Mara Basin of Kenya for purposes of supporting water resources development and ecological sustainability. The water flow processes – including the recharge rates and water loss processes – from existing sand storage systems were established through monitoring of ground and surface water levels. Water samples along the alluvial corridor were collected and analyzed for major ions and isotopic signatures required to establish the water storage dynamics. The storage potential was estimated through Probing and Electrical Resistivity Tomography techniques, augmented with in-situ measurements of hydraulic conductivities and channel bed porosities. The mean annual storage volume in the alluvium of the study reach was estimated at 1.1 Mm3, potentially capable of providing for the annual domestic and livestock water demands of the area. Transmission losses into the alluvium beneath the ephemeral channel-bed were noted to attenuate the flood peak discharges, depending on the level of saturation of the alluvial bed. However, water storage in the alluvium was subject to losses through evapotranspiration and seepage through fractured bedrocks. The study demonstrated the potential of alluvial corridors as water storage buffers providing alternative water sources to communities within the dry land regions with water scarcity, thereby to supporting ecosystem sustainability.